Phosphorus Removal from Eutrophic Waters with a Novel Lanthanum-Modified Diatomite - Xie, Fazhi; Da, Chunnian; Zhang, Fengjun; Zhang, Jun; Han, Xuan; Ge, Yejun; Li, Guolian (Asian Journal of Chemistry, 2013)
A novel phosphorus adsorbent, lanthanum-modified diatomite was prepared by a simple coating method and exhibited high adsorption and removal efficiency for phosphorus in aqueous solutions. After being modified by lanthanum hydroxide, the surface area of diatomite increased 85-fold and the pore volume increased 390 times. These characteristics are responsible for the increased phosphorus adsorption efficiency. Adsorption behaviour for phosphorus depended mainly on the pH of solution, contact time, initial P concentration and co-exist anion ions. The as-prepared sorbent can be used to remove phosphorus from eutrophic lake water efficiently.